The Effects of Gut Volume and Parity on the Pubis - Emma Long; Emma Piasecki; Jeanelle Uy; Natalie Laudicina (Humans)
The human pelvis is adapted to accommodate bipedal locomotion while retaining a wide enough pelvic canal to birth large babies. Many forces act on the pubic bone, with the pelvis being in charge of supporting the organs of the abdominopelvic cavity. In this research, we investigate whether increases in gut volume (GV) and number of births (parity) impact the skeletal morphology of the pubic bone at two regions: the pubic symphysis and the pubic arch. Our results indicate that in our female sample, the pubic symphysis width increased with increased GV and parity, while the pubic arch width decreased with increased GV and parity, although not significantly. In the male sample, there was almost no effect of increased GV on the pubic symphysis, while the pubic arch width increased in response to increased GV. We hypothesize that while significance is not present for this entire data set, these pelvic structures are impacted by GV and parity, and these changes should be investigated further. These changes in the structure can impact the function of the pelvic girdle and result in pain and changes to mobility. Pelvic girdle pain may be one result of these structural changes due to increased forces, and thus it is vital to investigate what factors may or may not contribute to these bone morphology changes.